The Porous Structure of Copper-cadmium Oxide System Prepared by AC Electrochemical Synthesis; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Dolinina A. S. Alesya Sergeevna; Korobochkin V. V. Valery Vasilievich; Usoltseva N. V. Natalia Vasilievna; Pugacheva S. E.; Popov M. V. (2015, 2015)
Title screen